L’estetica negli animali non umani - Marchesini, Roberto (Scenari, 2024)
Can we talk about a non-human aesthetic? Undoubtedly in our species aesthetics has taken on a particular ontological value and a cultural dimension that cannot be superimposed on that of other animals. However, it would be extremely wrong to believe that the sensorial and emotional orientation of other species can only be referred to mechanisms of behavioral stimulation or environmental monitoring. Ethological research has demonstrated for decades that Charles Darwin’s intuitions relating to aesthetic preferences in other species, at the basis of the evolution of some behaviors, such as sexual choice and courtship, found confirmation. Today we know that aesthetic stimuli induce specific physiological mechanisms, such as the activation of the dopaminergic system, and it is thus possible to study the sensory preference responses present in non-humans. These preferences are also demonstrated by other physiological mechanisms, such as the reduction of salivary cortisol in dogs when they listen to the human voice or the increase in milk production in cows if placed with classical music in the background. As with other aspects, we must therefore conclude that, if it is true that the aesthetic dimension in humans has had a development that goes beyond the mere ethological condition, it is undeniable that the bases of aesthetic behavior are part of the animal repertoire.